ANALISIS PELAKSANAAN SISTEM INFORMASI KESEHATAN DI KLINIK MUHAMMADIYAH MEDICAL CENTER (MMC) UNIVERSITAS MUHAMMADIYAH SURAKARTA - Noor Alis Setiyadi; Fahmi Hakam (Jurnal Ilmu Kesehatan Masyarakat, 2015)
Health information system is one of the six building blocks or key components of the health system. MMC is a health care unit at the Muhammadiyah University of Surakarta. This study purposed to determine the application of Health information system in MMC. This study was a qualitative research with System Development Life Cycle (SDLC) approach. Data collections were obtained by in-depth interviews and direct observation. The results of the research that has been done, that the existing health information system is not running well, because in the process of recording and reporting is still done manually, the lack of security of data, lack of data integration, as well as the information generated is not in accordance with the need for decision-making.Keywords : HIS, reporting, input, SDLC